Effect of Aerobic and Muscular Endurance Training On Physical Fitness, Physiological Variables and Body Composition of Sports Person - Vipul Shimpi; Dr Bharat Kumar Chaudhari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This study investigates the impact of aerobic and muscular endurance training on various physical fitness parameters, physiological variables, and body composition of sports persons. The research includes an experimental approach involving a control and an experimental group, with pre-and post-training assessments. The findings aim to provide insights into optimizing training programs for athletes.